Multifunctional Chitosan-Copper Oxide Hybrid Material: Photocatalytic and Antibacterial Activities - Yuvaraj Haldorai; Jae-Jin Shim (International Journal of Photoenergy)
Chitosan (CS) anchored copper oxide (CuO) hybrid material was prepared by chemical precipitation method. Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) confirmed the formation of CS-CuO hybrid. Transmission electron microscopy (TEM) analysis showed the immobilization of CuO nanoparticles on the surface of CS. The hybrid was also characterized by thermogravimetric analysis (TGA) and zeta potential. The hybrid exhibited high photocatalytic activity as evident from the degradation of methylene blue (MB) dye. The result revealed substantial degradation of the MB dye (84%) under UV-light illumination. The antibacterial activity of hybrid against Escherichia coli was examined by colony forming units. It was proved that the CS encapsulated CuO hybrid exhibited excellent antibacterial activity.